Employee Empowerment, Psycological Contract, Employee Engagement di Universitas di Indonesia - Mohammad Benny Alexandri; Nenden Kostini; Erna Maulina (Universitas Padjadjaran, 2019)
Some of the problems faced by lecturers in higher education are the lack of time for research because of teaching. Another problem is: a career as a lecturer is an endpoint or basis for a career elsewhere? The question is that the position of lecturer or being a Professor is still something interesting, prestigious, or not? Padjadjaran University is the number 6 Best University in Indonesia in QS World version in 2018. The number of lectuJrers is 1780 Lecturers. The purpose of this research is to find out Employee Empowerment, Psychological Contract and Employee Engagement at Padjadjaran University. The unit of analysis is 65 Permanent Lecturers at Padjadjaran University. The results of this study found that the effect of Employee Empowerment, Psycological Contract on Employee Engagement was only 15%. This indicates that the Padjadjaran University Lecturer does not yet have a strong Empowerment and Psychological Contract to produce a strong attachment to the University.